Assessment of the localization error of radio-acoustic bug devices by means of acoustic distance measurement - Oleynikov, A.N.; Lykov, Yu.V.; Zabolotnyi, V.I. (Radiotekhnika, 2024)
Localization of a radio-acoustic bug device (RABD) is the determination of its location in space. Localization of the RABD can be carried out both by the electromagnetic field and by using acoustic probing signals. Localization using acoustic probing signals is carried out using an acoustic rangefinder (AR) as part of a hardware-software complex (HSC) for detecting RABD (for example, the «ORT», «VOSTOK» hardware systems developed at KNURE). The operating principle of AR is given in the article. The error in measuring the coordinates of the RABD with an acoustic rangefinder consists of instrumental and random errors in measuring the range, as well as the methodological error in determining the location of the RABD, which is due to the peculiarities of the rangefinder method of determining coordinates. The article addresses the issue of minimizing the error in measuring the range of a bug device with an uncertainty of location by analyzing various methods for fixing the temporary position of an acoustic signal in real conditions for detecting radio-acoustic embedded devices in designated premises. The advantages and disadvantages of various methods for fixing the time position of an acoustic signal along one of the pulse fronts are analyzed simultaneously on the leading and falling edges of the pulse, at the position of the maximum signal values and using the correlation method of fixing the time position of the signal in relation to the localization of radio-acoustic bug devices in real conditions. The results of mathematical modeling and experimental research using the HSC “VOSTOK” of the error in determining the range to a radio-acoustic bug device are presented. It has been established that when localizing bug devices using an acoustic range finder, it is advisable to use the correlation method of fixing the time position of pulses. At the same time, there is a decrease in the standard deviation of the localization error compared to the threshold method by 15% in the range of s/n values from 2 to 20, high stability of the results and low sensitivity to changes in the amplitude of the received signal.